Solar Space Cooling and Heating and Hot Water Production for a House - Kalogirou, Soteris A. (My University, 2005)
Heating and cooling of buildings require a large amount of energy. For countries with good solar potential, solar energy can be considered a viable option for these applications. With the increased price of fuels solar space heating became a viable option however the potential problem of such a system is that a lot of solar energy collectors need to be disconnected or shaded during summertime. Solar cooling offers possibilities of using the same solar collectors for space cooling as well through an absorption chiller. To be viable solar space heating systems need to utilize a low temperature supply system such as air system. Absorption units on the other hand require temperature of the order of 90°C but the system during summertime is more effective and the available solar radiation is much more than the wintertime. A system suitable for a typical 196 m2 house is modelled and simulated with TRNSYS program. The house is located in Nicosia, Cyprus, 35° North latitude having mild winters and severe summers. Three different types of solar collectors are considered a flat plate, advance flat plate and evacuated tube collectors. The results show that the optimum system consists of 1.5 m3 storage tank and 30 m2 evacuated tube collectors installed at an inclination equal to 30° and operated at a water flow rate of 36 kg/hr-m2. The annual solar contribution is about 55% and the economic analysis performed showed the system is viable as positive life cycle savings are obtained (5100 Euro). Therefore it can be concluded that solar energy should be used whenever possible.
Keywords: Heating buildings; Cooling of buildings; Solar energy; Solar cooling